Content creation for voice assistants and smart speakers: A challenge for non-English language media - Crespo, M.; Andrade, Wanessa (Fourth INTERNATIONAL WORKSHOP ON ENTREPRENEURSHIP, ELECTRONIC AND MOBILE BUSINESS, 2020)
In the last decade, voice assistants are becoming more and more popular. First with smartphones, artificial intelligence driven voice assistants become common for many persons. But with the launch of Amazon’s Alexa home devices, and then Google Nest, a new category of smart speakers started to invade our homes, always ready to answer their owners voice commands. In the last two years the use of smart devices almost doubled, showing this is a trend to watch, and the Covid-19 pandemic caused an increase in its use. These new interactive devices created new opportunities and challenges for content creators. In one hand, this is one of the most natural interfaces available – the user just has to speak – but to sort out what kind of answer he expects from the device is not straight forward. Media outlets are no exception in the discovery and exploration of these voice interfaces, which pose new questions and rules, making content creators to go deep into new challenges, first trying to sort out how to interact with users, then to discover what contents should be tailored to each user and, finally, the format of the news stories more adequate to voice. Through the analysis of the Portuguese language countries – with focus in Portugal and Brazil – we will try to sort the main challenges and problems that non-English media can face to create and deliver news though smart assistants.